2019
DOI: 10.1089/cyber.2019.0255
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Excessive Smartphone Use on Stress and Loneliness: The Moderating Role of Self-Disclosure

Abstract: The present study investigates how excessive smartphone use predicts users' stress and loneliness while taking the moderating role of online self-disclosure into account. We conducted a two-wave panel survey with a quota sample of smartphone users (n = 461 at time 2 [T2]). We found no direct effects of excessive smartphone use on stress or loneliness. However, our results showed that online self-disclosure moderates the postulated relationships. That is, excessive smartphone use (time 1 [T1]) predicts increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 62 publications
1
42
0
4
Order By: Relevance
“…30,31 One small longitudinal study suggested that even heavy smartphone use was protective against loneliness when participants used these tools to engage in self-disclosure with peers. 32 Private messaging necessitates a specific, known recipient, perhaps indicating a greater degree of familiarity or closeness. This type of social media engagement may therefore serve to strengthen existing social networks.…”
Section: In Recent Years Frison and Eggermont Distinguished Between Pumentioning
confidence: 99%
“…30,31 One small longitudinal study suggested that even heavy smartphone use was protective against loneliness when participants used these tools to engage in self-disclosure with peers. 32 Private messaging necessitates a specific, known recipient, perhaps indicating a greater degree of familiarity or closeness. This type of social media engagement may therefore serve to strengthen existing social networks.…”
Section: In Recent Years Frison and Eggermont Distinguished Between Pumentioning
confidence: 99%
“…However, longitudinal studies are scarce, and all existing longitudinal studies recruited convenient samples rather than surveying the clinical population [23][24][25][26]. The pre-existing longitudinal studies are limited by drawing conclusions exclusively by conducting surveys on non-clinical convenient samples.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Volkmer and Lermer (8) reported cellphone dependency and overuse as the reason for psychological harm like anxiety. In this case, individuals feel stress and restless when losing their phones (30).…”
Section: Discussionmentioning
confidence: 99%